FILSAFAT AKHLAK DALAM KONTEKS PEMIKIRAN ETIKA KONTEMPORER - Basyir Mardjudo (Hunafa: Jurnal Studia Islamika, 2005)
Ethics is one of Islamic fundamental teachings. It is recommended by Islam because Islam is a peace religion. Muslims believe that it is because of the prophet Muhammad’s ethics that Islam can be voluntarily accepted by people. It is within this context that this article tries to explore Islamic teaching on ethics and peace either to Muslims or non-Muslims. Kata kunci: Filsafat Akhlak, Etika